The Effect of Perceived Ease, Perceived Benefits, and Sales Promotion on Intention to Use with Consumer Behavior as a Moderating Variable in Using Digital Wallets - Hulu, Gracelin Nonifati; Manulang, Dea Lonita; Gultom, Parapat (Talenta Publisher, 2024)
This study aims to determine the effect of perceived convenience, perceived benefits, and sales promotions on intention to use and consumer behavior in using digital wallets in Medan. Perceived convenience, perceived benefits and sales promotion as independent variables, while intention to use as the dependent variable. This study uses a type of quantitative research, data processing methods using the SmartPLS 4.0 (Partial Least Square) program. The population of this study were all digital wallet users in Medan. The sample was determined by the purpose sampling method, with a sample of 100 respondents. The sample used is Digital Wallet users in Medan. The results of this study indicate that the perceived usefulness variable has no significant effect, while the benefit variable and sales promotion have a significant effect on the intention to use a Digital Wallet.